Efficacy of cryotherapy as first line therapy in patients with Barrett's neoplasia: a systematic review and pooled analysis. Issue 11 (10th May 2019) - Hamade, N; Desai, M; Thoguluva Chandrasekar, V; Chalhoub, J; Patel, M; Duvvuri, A; Gorrepati, V S; Jegadeesan, R; Choudhary, A; Sathyamurthy, A; Rai, T; Gupta, N; et al.
SUMMARY: Cryotherapy has been used as salvage therapy; however, its efficacy as first line treatment in patients with Barrett's esophagus (BE) neoplasia has not been well studied. The aim of this paper was to perform a systematic review to look at the efficacy of cryotherapy as the primary treatment of BE. An electronic database search was performed (PubMed, Embase, Cochrane, and Google Scholar) to search for studies with cryotherapy as the initial primary modality of ablation in patients with BE neoplasia. Studies that included patients with other prior forms of therapy were excluded. The primary outcomes were the pooled rates of complete eradication of intestinal metaplasia (CE-IM) and CE of neoplasia (CE-N). Secondary outcomes were recurrence rates of neoplasia and intestinal metaplasia (IM) and adverse events. The statistical software OpenMetaAnalyst was used for analysis with pooled estimates reported as proportions (%) with 95% confidence intervals (CI) with heterogeneity ( I 2 ) among studies. The search revealed 6 eligible studies with a total of 282 patients (91.5% male, average age 65.3 years) with 459 person years of follow-up. 69.35% [95% CI (52.1%–86.5%)] of patients achieved CE-IM and 97.9% (95% CI: 95.5%–100%) had CE-N. 7.3% of patients had persistent dysplasia with 4% progressing to cancer. The recurrence rate of neoplasia was 10.4 and that of IM was 19.1 per 100 patient years of follow-up. The overall rate of stricture formation was 4.9%. There are scarce data on the use of cryotherapy as the primary modality for the treatment of BE dysplasia. The published data demonstrate efficacy rates of 69% and 98% for complete eradication of metaplasia and neoplasia, respectively. These results need to be assessed in prospective, comparative trials with other forms of therapy.